KEPEMIMPINAN STRATEGIS: PENGEMBANGAN KAPASITAS SUMBER DAYA (STUDI KASUS DI RS ISLAM JAKARTA, CEMPAKA PUTIH) - Gani, Nur Asni; Marfuah, Umi; Casban, Casban; Maulianza, Medo (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
The study focuses on strategic leadership in developing human resource capacity at the Jakarta Islamic Hospital, Cempaka Putih. Hospitals as complex organizations require competent human resources to be able to compete in this competitive era. The study was analyzed using an interpretive qualitative method by conducting in-depth interviews with two informants who are the top leaders of the hospital, namely the Director of Human Resources and the Director of Finance at the Jakarta Islamic Hospital, Cempaka Putih. The results of the study indicate that the hospital's strategic leadership towards human resource development is in the form of leadership commitment in human resource development starting from the selective recruitment process with established measuring tools and the process of developing existing human resource capacity. Leaders also motivate all employees from the managerial level to the staff in various meetings. Finally, leaders provide appreciation to employees in both cash and non-cash forms in the form of training and education.Keywords : strategic leadership, hospital